Contemporary computing Third International Conference, IC3 2010, Noida, India, August 9-11, 2010, proceedings, part I - International Conference on Contemporary Computing (Communications in Computer and Information Science, 2010)
This book constitutes the first part of the refereed proceedings of the Third International Conference, IC3 2010, held in Noida, India, in August 2010. The 23 revised full papers presented were carefully reviewed and selected from numerous submissions. Technical session-1: Algorithm-1 (A-1) - A PDE-based nonlinear filter adapted to Rayleigh’s speckle noise for De-speckling 2D ultrasound images - Face recognition using kernel fisher linear discriminant analysis and RBF neural network - Parallel enumeration sort on OTIS-Hypercube - A robust trust mechanism algorithm for secure power aware AODV routing in mobile Ad Hoc networks - A heuristic algorithm for constrained redundancy optimization in complex systems - Technical Session-2: Algorithm-2 (A-2) - A hybrid genetic algorithm based test case generation using sequence diagrams - LACAIS: Learning Automata Based Cooperative Artificial Immune System for Function Optimization - Image reconstruction from projection under periodicity constraints using genetic algorithm - A robust watermarking algorithm for audio signals using SVD - Differential evolution using interpolated local search - Technical Session-3: Algorithm-3 (A-3) - A new SVD based watermarking framework in fractional fourier domain - Mining frequent and associated gene expression patterns from spatial gene expression data: a proposed approach - Minimization of lennard-Jones potential using parallel particle swarm optimization algorithm - An artificial bee colony algorithm for the 0–1 multidimensional knapsack problem - Automatic summary generation from single document using information gain - Technical Session-4: Algorithm-4 (A-4) - An alternate approach to compute the reliability of a computer communication network using binary decision diagrams - A multi-level blocks scrambling based chaotic image cipher - Maxillofacial surgery using x-ray based face recognition by elastic bunch graph matching - A phenomic approach to genetic algorithms for reconstruction of gene networks - An algorithm to determine minimum velocity-based stable connected dominating sets for Ad Hoc networks - Technical Session-5: Algorithm-5 (A-5) An efficient instrusion detection system using clustering combined with logic - Assessing the performance of bi-objective MST for Euclidean and Non-Euclidean instances - PSO - SVM based classifiers: a comparative approach - Efficient job division for grids running SIMD algorithms - A novel algorithm for achieving a light-weight tracking system - Technical Session-6: Application-1 (P-1) - Computer simulation studies of drug-DNA interactions: Neothramycin B - Effect of speech coding on recognition of Consonant-Vowel (CV) units - Cloudbank: a secure anonymous banking cloud - Alignment model and training technique in SMT from english to Malayalam - Emotion classification based on speaking rate - Technical Session-7: Application-2 (P-2) - A vulnerability metric for the design phase of object oriented software - A framework for synthesis of human gait oscillation using Intelligent Gait Oscillation Detector (IGOD) - Detection of significant opinionated sentence for mining web users’ opinion - Hyperspectral data ccmpression model using SPCA (Segmented principal component analysis) and classification of rice crop varieties - Impulse noise removal from color images using adaptive neuro–fuzzy impulse detector - Technical Session-8: Application-3 (P-3) - Measuring of time-Frequency Representation (TFR) content – Using the Kapur’s entropies - An ontology based framework for domain analysis of interactive system - Entropy based clustering to determine discriminatory genes for microarray dataset - A framework for incremental domain-specific hidden web crawler - Impact of K-Means on the performance of classifiers for labeled data - Technical Session-9: Application-4 (P-4) - Digital watermarking based stereo image coding - Content based multimodal retrieval for databases of indian monuments - Evolutionary based automated coverage analysis for GUI testing - Online signature classification using modified fuzzy Min-Max neural network with compensatory neuron topology Multifaceted classification of websites for goal oriented requirement engineering - Technical Session-10: Application-5 (P-5) - A simplified and corroborative approach towards formalization of requirements - Robust multiple watermarking using entropy based spread spectrum - Application of adaptive learning in generalized neuron model for short term load forecasting under error gradient functions - Intelligent schemes for indexing digital movies - Fuzzy reasoning boolean petri nets based method for modeling and analysing genetic regulatory networks - Technical Session-11: Application-6 (P-6) - Mining the blogosphere for sociological inferences - Modeling for evaluation of significant features in siRNA design - A fast progressive image transmission algorithm using linear bivariate splines - Building optimization - Adaptive bacterial foraging optimization based tuning of optimal PI speed controller for PMSM drive - Missing value imputation based on k-mean clustering with weighted distance.